Exploring EFL Teacher 'Strategies to Accomodate Students'Learning Styles - Andi khofifah Andi Pogeng; Sukardi Weda; Muhammad Hasbi (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
Teaching English in classes where students have different learning styles poses special challenges for teachers. Some students learn better through visual aids, others through listening, speaking, or moving actively. Therefore, understanding and applying appropriate teaching strategies to accommodate these diverse learning styles is essential. This study aims to explore the strategies used by an EFL teacher to address students’ varied learning preferences in an English classroom at SMAN 2 Pangkep. This research employed a qualitative descriptive study design. The subject of this study was one English teacher who teaches tenth-grade students. Data were collected through classroom observation and interviews, the strategies used by the teacher include using pictures and illustrations, referring to textbooks with visuals, occasional use of the internet, and encouraging group discussions. The findings reveal that these strategies helped maintain student engagement and supported different learning styles, even though the teacher did not formally assess them. This study highlights the importance of teacher awareness and adaptability in meeting students’ varied ways of learning in the EFL context.